PENGARUH FAKTOR-FAKTOR FUNDAMENTAL TERHADAP KUALITAS PENGUNGKAPAN SUKARELA DALAM LAPORAN TAHUNAN PADA PERUSAHAAN MANUFAKTUR YANG TERDAFTAR DI BURSA EFEK INDONESIA - Budianto, Arief Satrya (Jurnal Akuntansi Kontemporer, 2009)
The purpose of this research is to find the fundamental factors that influence voluntary disclosure published in ar:nual reports. This research used 22 manufacturing companies listed at Indonesia Stock Exchange in the period of 2006-2007, is chosen by pwposive sampling. Multiple regression analysis was employed to test the research hypothesis. The result of this research show that none of the independent variables in/hence voluntary disclosure published in annual report.